Soil biodiversity enhances the persistence of legumes under climate change. Issue 5 (8th December 2020) - Yang, Gaowen; Roy, Julien; Veresoglou, Stavros D.; Rillig, Matthias C.
Summary: Global environmental change poses threats to plant and soil biodiversity. Yet, whether soil biodiversity loss can further influence plant community's response to global change is still poorly understood. We created a gradient of soil biodiversity using the dilution‐to‐extinction approach, and investigated the effects of soil biodiversity loss on plant communities during and following manipulations simulating global change disturbances in experimental grassland microcosms. Grass and herb biomass was decreased by drought and promoted by nitrogen deposition, and a fast recovery was observed following disturbances, independently of soil biodiversity loss. Warming promoted herb biomass during and following disturbance only when soil biodiversity was not reduced. However, legumes biomass was suppressed by these disturbances, and there were more detrimental effects with reduced soil biodiversity. Moreover, soil biodiversity loss suppressed the recovery of legumes following these disturbances. Similar patterns were found for the response of plant diversity. The changes in legumes might be partly attributed to the loss of mycorrhizal soil mutualists. Our study shows that soil biodiversity is crucial for legume persistence and plant diversity maintenance when faced with environmental change, highlighting the importance of soil biodiversity as a potential buffering mechanism for plant diversity and community composition in grasslands.